Lohmannella consimilis Bartsch 1993 - Abé, Hiroshi (Zenodo, 2021)
Lohmannella consimilis Bartsch, 1993 Diagnosis. One cornea present. Glp-1 posterior to Ds-1. Ds-2 on membranous cuticle. Ds-3 on margin of PD. Two dorsal setae on PE. Female with 16–18 Pgs and 8 Sgs. Tr I–IV with 1-1-1-1 setae; Bf I–IV with 3-3-(3,4)-3 setae; Tf I–IV with 7-7-5-4 setae; Gn I–IV with 8-(7,8)-4-4 setae, 4-0-0-0 Bp setae; Tb I–IV with (12,13)-11-(6,7)-7 setae, 6-5-(2,3)-3 Bp setae; Ta I–IV with 3-3-4-3 dorsal setae, 2-2-2-2 Bp setae. Lc I with unidentate accessory process. Idiosoma length 385 in female. Idiosoma width 307 (idiosoma length 385) in female. Gnathosoma length 230 (idiosoma length 385) in female. Ratio of gnathosoma to idiosoma 0.60 in female. Ratio of P-2 to P-1 3.00. Remarks. The species is distinguished from the other Antarctic species by the pyriform PD, lacking of epicuticular reticulation and porous areolae on dorsal plates. Female is known. Habitat. Sublittoral zone: Bottom sediment at 100 m depth. Distribution. South Atlantic Ocean: South Sandwich Is. [UK]. Reference. Bartsch (1993b). Depository. USNMNHW. : Published as part of Abé, Hiroshi, 2021, Taxonomic review of the subfamily Lohmannellinae (Acari: Trombidiformes Halacaridae) with morphological comparisons among genera, pp. 201-255 in Zootaxa 4980 (2) on page 210, DOI: 10.11646/zootaxa.4980.2.1, http://zenodo.org/record/4888860 : {"references": ["Bartsch, I. (1993 b) Synopsis of the Antarctic Halacaroidea (Acari). In: Wagele, J. W. & Sieg, J. (Eds.), Synopses of the Antarctic Benthos, Volume 4, Koeltz Scientific Books, Koenigstein, pp. 1 - 176."]}